A tese da incomensurabilidade teórica em Paul Feyerabend - Luiz Henrique de Lacerda Abrah?o (2009)
The present work outlines a reflection on the genesis, the structure and the assumptions behind the incommensurability thesis proposed by Austrian philosopher Paul Feyerabend (1924-1994). The research is greatly aimed at the discussion of the formative elements of the concept as well as its epistemological constitution and methodological repercussions. The body of the work is laid out according to a methodological arrangement in which Feyrabends writings are organized in three chronological building blocks. Firstly, it is evaluated the role that the reflections by Wittgenstein, Duhem and Hanson regarding the contextual character of the scientific concepts and observations played at the conceptualization of the proto-version of incommensurability. Furthermore, it is evaluated how the Thesis I, defended by Feyerabend in 1958, which states that the observational language is determined by the theories which we use to explain what we observe, goes against the double-language model of scientific vocabulary. Secondly, it is displayed the defining methodological and historical arguments of the incommensurability thesis present in the seminal Feyerabends article Explanation, Reduction and Empiricism (1962). Moreover, it is tracked the origin of the criticism to the conditions of logical consistency and meaning invariance within Feyerabends divergence with Niels Bohr demand for preservation of classical vocabulary at the description of microphysical events. The resemblances and antagonisms between Feyerabend and Kuhn points of view regarded to the structure of scientific knowledge and the incommensurability thesis are also analyzed. Finally, it is overlooked the incommensurability thesis variations from the standpoint of the reformulation of the Feyerabends contextual theory of meaning and the debate with the Popperian model of scientific progress as verisimilitude increase of theories. The development of the concept in Against Method, the critical reception of the Feyerabends idea from the 1970s, and the final considerations of Feyerabend about the theme end the threefold core of this work. As a result, this work stands for the rejection of the irrational interpretations of the proposal of Feyerabend and presents how a hypothetical realism is assumed within his version of incommensurability thesis.